Ocular manifestations in kabuki syndrome: A report of 10 cases and literature review. (4th March 2021) - Cheon, Chong Kun; Choi, Hee Young; Park, Su Hwan; Jung, Jae Ho; Kim, Su Jin
ABSTRACT: Background : We investigated the ocular manifestations in patients with Kabuki syndrome(KS). Methods : A retrospective chart review was performed in 10 patients with KS were referred to the Department of Ophthalmology for evaluation of ocular manifestations. Data were collected from patient interviews, clinical examinations, and laboratory investigations. Ophthalmologic examinations included best-corrected visual acuity, intraocular pressure, anterior segment, adnexal examination, and dilated fundus examination. Results : Mutations in the KMT2D gene were identified in all of the 10 patients with KS. No deletion or point mutation was found in the KDM6A gene. In our patients, 20% had ptosis, 60% had strabismus, 90% had lid changes and 10% had amblyopia. Five patients did not undergo the visual acuity test due to intellectual disability. Conclusions : Ophthalmic abnormalities are frequently associated with KS. The importance of ophthalmological examination in all patients with KS for early detection of ocular anomalies to prevent visual impairment cannot be underemphasized. Abbreviations : KS: Kabuki syndrome